Pemberdayaan Usaha Lokal Melalui Pemasaran Digital untuk Meningkatkan Daya Saing Produk Unggulan Desa Kaligentong - Arum Marwati; Sintar Nababan; Nopriadi Nopriadi; Dhety Chusumastuti; Sigit Purnomo (Jurnal Kemitraan Masyarakat, 2025)
This Community Service (PkM) program was conducted in Kaligentong Village, Gladagsari, Boyolali, Central Java, aiming to enhance the competitiveness of local superior products through the implementation of digital marketing strategies for micro, small, and medium enterprises (MSMEs). The main problem faced by the partners was their limited ability to utilize social media and online marketplaces for effective product marketing. The program employed a two-day training approach, including product photography and videography using smartphones, promotional content writing (copywriting), and online store creation on e-commerce platforms, followed by hands-on mentoring and evaluation. The results showed a significant improvement in participants’ knowledge and skills in managing digital business accounts, producing engaging photo and video content, and utilizing marketplaces to expand their market reach. More than 80% of participants successfully created new business accounts and actively promoted their products online. This activity had a positive impact on improving digital literacy and local product marketing while strengthening the collaboration between higher education institutions and the community in developing the village economy.